The Early Childhood Development of Pediatric Burn Patients - Maxime D. Cuijpers; Moniek Akkerman; Martin G. A. Baartmans; Paul P. M. van Zuijlen; Anouk Pijpe (MDPI AG, 2024)
Our study aimed to provide a description of the early childhood development of pediatric burn patients relative to Dutch reference values, using both pre- and post-burn data from the Dutch Development Instrument and the D-score. Data from the Dutch Development Instrument were used to calculate the D-score and age-standardized D-score. Similar to a growth chart, the D-score was used to plot pediatric burn patients' development relative to Dutch reference values for their age. Pediatric burn patients' (n = 38) median age at the time of injury was 1.0 (1.0-2.0) years old. Burn size ranged from 1.0% to 36.0% of the total body surface area. Ninety-five percent (± 6.0%) of pediatric burn patients passed each of the age-appropriate developmental milestones at the target age. The mean age-standardized D-score was just above the Dutch average (+0.49 SD [0.18, 0.80]) and did not vary depending on sex (p = 0.06) or burn size (p = 0.41). In conclusion, among pediatric patients aged up to two-and-a-half years old, with non-full thickness burns, development was on track relative to the Dutch reference values. Our findings offer valuable first insights into the early childhood development of pediatric burn patients and may alleviate some parental concerns.